Smart Sprawl? Green Aspirations and the Lowdown on High-Density Suburbia - Pavone, Paige (Columbia Journal of Environmental Law, 2019)
Reading Woods, an expensive condominium development north of Boston, is a quintessential example of suburban sprawl. Built in 2011, Reading Woods comprises 408 units, with unlimited parking for each. From Reading Woods, residents cannot walk to a public library, a bank, or a grocery store; they often opt to drive to the nearby strip mall instead. If they really wanted to, residents could walk to a chain restaurant, but they would have to risk crossing I-95 first. I-95 is familiar to them-a backyard of sorts-rushing past 100 feet away. Given these facts, it is perplexing that a Smart Growth Overlay District enabled the development of Reading Woods. Many hail high-density development as the smart growth solution to sprawl. While mixed-use high-density and urban residential high-density may be valid solutions, exclusively residential high-density suburban development is anything but smart. Ironically, developers build these High-Density Islands, as I will refer to them, using the legal techniques developed for smart growth programs. However, smart growth tools depend on co-implementation to achieve their purported benefits. When applied individually, smart growth and anti-sprawl programs can yield exclusively residential high-density suburban development. Thus, High-Density Islands merely add density to suburban sprawl and exacerbate the very problems smart growth seeks to correct. Without public infrastructure to accommodate low-carbon-emitting lifestyles for the additional and existing residents, High-Density Islands deepen suburbia’s car-dependency. High-Density Islands spur other critical problems that enfeeble efficacious land use planning, such as civic disengagement, high public costs, homogeneity, bromidic buildings, public health hazards, and environmental justice concerns. The construction of High-Density Islands cannot continue without crippling America’s physical and cultural environment.